Membawa Keadilan Bagi Identitas-Diri Orang Papua - Stephanus Djunatan (Jurnal Administrasi Publik, 2014)
Bringing justice and peace to the Papuans would not be complete without the attention to any internal or private aspects of the Papuans. Efforts to improve the lives of the people of Papua such as building infrastructure facilities, education, health, security and law enforcement needs to be equiped with an appreciation of the fundamental aspects of the tribes in Papua and their culture. The fundamental aspect is the Papuans identity appreciation. This article intends to conceive how the identity appreciation of the Papuans should occur. Cultural and philosophical approach to the aspects of self-identity shows that the appreciation of the self-identity of the Papuan People is associated with the idea that everyone is existentially equal. We are not equivalent because of the legal aspects of such orders, not because of religious or advise it. Therefore, this paper is divided into three sections: the first section describes the philosophical-cultural approach to self-identity aspects. The second part initiate stigmatic stereotypes and perceptions that build ethnic identity in the archipelago, including the identity of the Papuans. The third discusses the appreciation of self-identity of the Papuans, which becomes a central issue for efforts in building prosperity or bringing justice and peace to the people of West Papua.